Comparative analysis of niobium and vanadium carbide efficiency in the high energy mechanical milling of aluminum bronze alloy - Dias,Alexandre Nogueira Ottoboni (2018)
Abstract This study aims to analyze the efficiency of niobium and vanadium carbides in the high energy mechanical milling of aluminum bronze alloy. Two series of experiments were made following the same steps for both niobium carbide (NbC) and vanadium carbide (VC) additions: 30 g of chips were weighed and placed in a stainless steel jar with 3 % of carbide and 1 % of stearic acid for a mass/sphere relationship of 1:10. The milling was realized using a planetary ball mill for 10, 30 and 50 hours in an inert argon atmosphere at 300 rpm. Results shown in laser diffraction indicate a great reduction in the particle sizes of powders when VC is used. For 30 hours milling, D50 values ranged from 1580 µm with NbC to 182.3 µm with VC addition. The D50 values ranged from 251.5 µm with NbC to 52.26 µm with VC addition, for 50 hours milling. The scanning electron microscopy showed that in 10 hours of milling, the energy was not sufficient to achieve the shear of chips in both cases. For 30 hours, it's possible to observe particles with sizes between 100 µm and 800 µm with NbC addition while for the same milling time, with VC it's possible to see particles with different sizes, but with many shapes of fine particulates. For 50 hours milling, particles achieved the smaller sizes between 50 and 200 µm with NbC and ranging from 5 until 50 µm with VC addition.